2006
DOI: 10.1007/s11134-006-5223-1
|View full text |Cite
|
Sign up to set email alerts
|

Tail asymptotics for the queue length in an M/G/1 retrial queue

Abstract: In this paper, we study the tail behavior of the stationary queue length of an M/G/1 retrial queue. We show that the subexponential tail of the stationary queue length of an M/G/1 retrial queue is determined by that of the corresponding M/G/1 queue, and hence the stationary queue length in an M/G/1 retrial queue is subexponential if the stationary queue length in the corresponding M/G/1 queue is subexponential. Our results for subexponential tails also apply to regularly varying tails, and we provide the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…On the other hand, there are recent works on heavy-tailed asymptotics in the M/G/1 retrial queue: Shang et al [14] showed that the stationary distribution of the queue length in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue length in the corresponding ordinary M/G/1 queue is subexponential. As a corollary of this property, Shang et al proved that the stationary distribution of the queue length in the M/G/1 retrial queue has a regularly varying tail if the service time distribution has a regularly varying tail.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are recent works on heavy-tailed asymptotics in the M/G/1 retrial queue: Shang et al [14] showed that the stationary distribution of the queue length in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue length in the corresponding ordinary M/G/1 queue is subexponential. As a corollary of this property, Shang et al proved that the stationary distribution of the queue length in the M/G/1 retrial queue has a regularly varying tail if the service time distribution has a regularly varying tail.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [10] showed that the tail of the queue size distribution is asymptotically given by a geometric function multiplied by a power function. On the other hand, Shang et al [16] and Kim and Kim [9] studied heavy-tailed asymptotics in the M/G/1 retrial queue. Shang et al [16] showed that the stationary distribution of the queue size in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue size in the corresponding ordinary M/G/1 queue is subexponential.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Shang et al [16] and Kim and Kim [9] studied heavy-tailed asymptotics in the M/G/1 retrial queue. Shang et al [16] showed that the stationary distribution of the queue size in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue size in the corresponding ordinary M/G/1 queue is subexponential. As a corollary of this property, they proved that the stationary distribution of the queue size has a regularly varying tail if the service time distribution has a regularly varying tail.…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, [5,6,11,16] and references therein. However, for the heavy-tailed asymptotics in retrial queues, it seems that Shang et al [15] is the only known result in the open literature. Shang et al [15] showed that the stationary distribution of the queue length in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue length in the corresponding ordinary M/G/1 queue is subexponential.…”
mentioning
confidence: 99%
“…However, for the heavy-tailed asymptotics in retrial queues, it seems that Shang et al [15] is the only known result in the open literature. Shang et al [15] showed that the stationary distribution of the queue length in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue length in the corresponding ordinary M/G/1 queue is subexponential. As a corollary of this property, they proved that the stationary distribution of the queue length has a regularly varying tail if the service time distribution has a regularly varying tail.…”
mentioning
confidence: 99%